Brand Loyalty Drives Organic Vegetable Repurchase Through Digital Service Quality : Loyalitas Merek Mendorong Pembelian Ulang Sayuran Organik Melalui Kualitas Layanan Digital - Nur Komariyah; Wahyu Santoso; Gyska Indah Harya (Indonesian Journal of Innovation Studies, 2026)
General Background: The expansion of organic food commerce and e-commerce has intensified competition among digitally operated agribusinesses, but market growth does not automatically secure repeat purchasing. Specific Background: Twelve’s Organic relies on Instagram, Facebook, and WhatsApp, while 40.2% of 199 recorded customers purchased only once during 2024–2025, indicating unresolved retention problems. Knowledge Gap: Evidence integrating content marketing, online service quality, brand loyalty, and repurchase behavior within the fresh organic vegetable sector remains limited. Aims: This study examines the direct relationships among these constructs and tests brand loyalty as a mediating mechanism. Results: A quantitative survey was conducted with 90 purposively selected customers and analyzed using PLS-SEM in SmartPLS 4.0. Content marketing was positively associated with brand loyalty (β = 0.469, p < 0.001) and repurchase behavior (β = 0.342, p < 0.001). Online service quality was positively associated with brand loyalty (β = 0.475, p < 0.001) and repurchase behavior (β = 0.291, p < 0.001). Brand loyalty was positively associated with repurchase behavior (β = 0.385, p < 0.001) and significantly mediated content marketing (β = 0.181, p = 0.001) and online service quality (β = 0.183, p < 0.001). The model explained 76.8% of brand loyalty and 88.9% of repurchase behavior. Novelty: The study integrates four constructs within one predictive model for a digitally operated fresh organic vegetable business. Implications: Twelve’s Organic should sustain relevant, accurate, accessible, and consistent content while providing responsive, reliable, secure, and customer-oriented online services to reinforce customer commitment and repeated purchasing. Highlights: Content strategy recorded direct coefficients of 0.469 for customer commitment and 0.342 for repeat buying. Online service quality recorded coefficients of 0.475 and 0.291 across the two outcomes. Customer commitment transmitted both indirect pathways, while the model explained 76.8% and 88.9% of outcome variance. Keywords: Brand Loyalty, Digital Marketing, E-Service Quality, Repurchase